Hydrothermal alkaline defluorination rate of perfluorocarboxylic acids (PFCAs). Issue 5 (15th February 2023) - Endo, Jun; Funazukuri, Toshitaka
Abstract: BACKGROUND: Although perfluoroalkyl and polyfluoroalkyl substances (PFASs), including perfluorocarboxylic acids (PFCAs), are used for various industrial and consumer products, they can cause serious damage to human health. Various defluorination/destruction methods have been investigated on the decomposition/removal of PFASs under low‐concentration conditions. These methods are not suitable for treating large amounts of contaminants or waste liquids with a high PFAS concentration. The hydrothermal alkaline defluorination (HAD) method has advantages, such as a relatively high reaction rate and a high recovery of halide ions in the aqueous phase. However, a few studies on the HAD method have been reported and they did not recover all the fluorine atoms/fluoride ions. Also, the reaction kinetics over a wide range of experimental conditions have not been studied. RESULTS: Perfluorooctanoic acid (PFOA) and PFCAs having 4 to 12 carbon atoms to 12 were subjected to aqueous NaOH solution under hydrothermal conditions, and the defluorination rates were found to be expressed by the second‐order reaction kinetics with respect to each concentration of OH − and fluorinated compound. The defluorination rate constants of both 4 to 12 carbon atom PFCAs at 553 K and PFOA at 513–573 K fall along a straight line in logarithmic plot. This suggests that the mass transfer of PFCAs or PFOA between the vapor and liquid phases can strongly affect the defluorination reactions. CONCLUSION: The HAD rates of PFCAs were determined and suggested to be significantly affected by mass transfer of PFCAs between vapor and liquid phases. © 2023 Society of Chemical Industry (SCI).